Microstructures and properties of welded joints of a duplex stainless steel - Ng, Chong Wei (2016)
Duplex stainless steel has many uses in the oil and gas industry, chemical processing industry and basically, manufacturing industries. It has many applications in pipping system and heat exchangers. It has higher corrosion, resistance ,higher mechanical strength higher resistance ,excellent weldability than other ferrite stainless steel.